Environmental and Host Characteristics Shape the Gut Microbiota of the Sand Field Cricket, Gryllus firmus - Divya Patel; Clint D. Kelly; Cassandre Sara Lazar (Applied Microbiology, 2024)
The gut microbiota plays an essential role in its host’s nutrition, development and behavior. Although crickets are becoming major ecosystemic model systems and have important societal applications, such as alternative animal proteins or biocatalysts, little is known about their gut microbiome acquisition and how environmental factors shape this community. Therefore, in this study, we exposed sand field crickets to soils with different characteristics and microbial communities to test the influence of these on gut microbial community composition. We used 16S/18S rRNA gene Illumina sequencing to analyze different soil and gut communities, targeting the three domains of life, Archaea, Bacteria, and Eukaryotes. Our results showed a dominance of Mucoromycota fungi and Bacteroidota in the gut microbiota. We were unable to retrieve sufficient read numbers for the Archaea. Most of the microbial taxa that were identified can degrade soil-derived complex organic matter, likely helping the host digest its food. The soil characteristics had a significant impact on the gut microbial community structure, supporting our assumption that the environment plays an essential role in gut microbiota acquisition. Host sex also had an impact on the gut community, possibly because the female guts were bigger in mass, leading to differences in oxygen concentrations.